Characterization of the cytochrome system of a nitrogen‐fixing strain of a sulfate‐reducing bacterium: Desulfovibrio desulfuricans strain Berre‐Eau - Moura, Isabel (2019)
Two c‐type cytochromes were purified and characterized by electron paramagnetic resonance (EPR) and nuclear magnetic resonance (NMR) spectroscopic techniques, from the sulfate‐reducer nitrogen‐fixing organism, Desulfovibrio desulfuricans strain Berre‐Eau (NCIB 8387). The purification procedures included several chromatographic steps on alumina, carboxymethylcellulose and gel filtration. A tetrahaem and a monohaem cytochrome were identified. The multihaem cytochrome has visible, EPR and NMR spectra with general properties similar to other low‐potential bis‐histidinyl axially bound haem proteins, belonging to the class of tetrahaem cytochrome c3 isolated from other Desulfovibrio species. The monohaem cytochrome c553 is ascorbate‐reducible and its EPR and NMR data are characteristic of a cytochrome with methionine‐histidine ligation. Their properties are compared with other homologous proteins isolated from sulfate‐reducing bacteria.